2022
DOI: 10.1029/2021gl095697
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Cooling is Slowing Down Mass Loss of Icelandic Glaciers

Abstract: Iceland is located on the Mid-Atlantic Ridge, marking the boundary between the North-American and Eurasian tectonic plates, with numerous active volcanoes and glaciers that cover about 10% of the island surface (Björnsson & Pálsson, 2008). Icelandic glaciers span elevations from sea level up to the highest peaks at ∼2,100 m a.s.l. (above sea level), are 340 m thick on average, and cover an area of roughly 11,000 km 2 (Björnsson & Pálsson, 2008. Iceland hosts four major ice caps (>500 km 2 ) including the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Between the desertic center of Greenland to the marine Russian archipelagos, the wide variety of climates across the Arctic cryosphere may mean that its response to climate change is not homogeneous spatially. This can be already shown by comparing the climate of the recent past in Greenland (Fettweis et al, 2017) and for example, Iceland (Noël et al, 2022). In the latter region, it has been shown that the North-Atlantic cooling has contributed to stabilizing the SMB of Iceland since 2010, while over Greenland melt rates were increased by the recurring atmospheric blocking situation gauged by negative NAO conditions.…”
Section: Correlation To Large Scale Indicesmentioning
confidence: 80%
“…Between the desertic center of Greenland to the marine Russian archipelagos, the wide variety of climates across the Arctic cryosphere may mean that its response to climate change is not homogeneous spatially. This can be already shown by comparing the climate of the recent past in Greenland (Fettweis et al, 2017) and for example, Iceland (Noël et al, 2022). In the latter region, it has been shown that the North-Atlantic cooling has contributed to stabilizing the SMB of Iceland since 2010, while over Greenland melt rates were increased by the recurring atmospheric blocking situation gauged by negative NAO conditions.…”
Section: Correlation To Large Scale Indicesmentioning
confidence: 80%
“…The polar (p) Regional Atmospheric Climate Model version 2.3p2 (RACMO2.3p2) incorporates the dynamical core of the High Resolution Limited Area Model (HIRLAM) 40 and the physics package cycle CY33r1 of the European Centre for Medium-Range Weather Forecasts-Integrated Forecast System (ECMWF-IFS) 41 . The model is specifically adapted to represent surface processes of polar ice sheets and ice caps including the Greenland ice sheet 30 , Canadian Arctic 33 , Svalbard 34 , Iceland 35 , and Antarctica 18 . The model incorporates a 40-layer snow module (up to 100 m depth) simulating melt, percolation and retention into firn and subsequent surface runoff 42 .…”
Section: Methodsmentioning
confidence: 99%
“…The ability of statistical downscaling to refine the spatial distribution of SMB components was first demonstrated for the Greenland ice sheet, where the downscaled product realistically captured high mass loss rates over narrow ablation zones and outlet glaciers that are typically unresolved in RACMO2.3p2 29 . Likewise, statistical downscaling to (sub-)kilometre spatial resolution proved essential to accurately quantify contemporary (and projected) mass change of the Greenland ice sheet 30 , 31 , its peripheral ice caps 32 , glaciers of the Canadian Arctic 33 , Svalbard 34 , and Iceland 35 , and their contribution to global sea-level rise. Using in situ and remote sensing data for model evaluation, we show that our downscaled product for Antarctica at 2 km improves upon the original RACMO2.3p2 data at 27 km, by resolving SMB and surface melt patterns in unprecedented spatial detail, notably in topographically rough regions including mountain ranges and the vicinity of the grounding line.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, this rate of decline has increased, with half of the total mass loss since the LIA having occurred since 1994 (Aðalgeirsdóttir et al, 2020). Although Iceland is particularly susceptible to ice mass loss, as the effects of climate change are amplified in polar regions (Holland & Bitz, 2003), the rate of deglaciation has been reduced since 2011 as a result of North Atlantic regional cooling (Noël et al, 2022). Iceland's volcanic activity also plays an important role in controlling glacier retreat, with volcanic dust and tephra affecting the albedo of ice caps and geothermal activity contributing to subglacial melt (Aðalgeirsdóttir et al, 2020; Boy et al, 2019; Gunnarsson et al, 2020; Meinander et al, 2021; Möller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, this rate of decline has increased, with half of the total mass loss since the LIA having occurred since 1994 (Aðalgeirsd ottir et al, 2020). Although Iceland is particularly susceptible to ice mass loss, as the effects of climate change are amplified in polar regions (Holland & Bitz, 2003), the rate of deglaciation has been reduced since 2011 as a result of North Atlantic regional cooling (Noël et al, 2022).…”
mentioning
confidence: 99%